2019
DOI: 10.2174/1874944501912010276
|View full text |Cite
|
Sign up to set email alerts
|

Views of Adolescent Girls on the Use of Implanon in a Public Primary Health Care Clinic in Limpopo Province, South Africa.

Abstract: Background: Implanon is one of the contraceptives that protects women from falling pregnant for a period of 3 years. Levonorgestrel implants are perfect for adolescents who wish to have lengthy protection against pregnancy and for those who are not consistent in taking Oral Contraceptive Pills (OCP). Objective: The objective of the study is to investigate the views of adolescent girls on the use of Implanon as a birth control method. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…In alignment with this study findings, Mkansi 9 found that secondary school-going girls at Bokamoso School in Polokwane District had insufficient knowledge about Implanon, how it works and its side effects. 10 Rabopape et al 11 revealed similar findings to this study, which showed that a lack of knowledge about Implanon’s side effects, hence contributed to low uptake by adolescent girls in the Limpopo province. 9 Adeagbo et al 12 concurred with this study finding, as women required detailed and evidence-based counselling that encompasses the likely side effects and other features of the method.…”
Section: Discussionsupporting
confidence: 85%
“…In alignment with this study findings, Mkansi 9 found that secondary school-going girls at Bokamoso School in Polokwane District had insufficient knowledge about Implanon, how it works and its side effects. 10 Rabopape et al 11 revealed similar findings to this study, which showed that a lack of knowledge about Implanon’s side effects, hence contributed to low uptake by adolescent girls in the Limpopo province. 9 Adeagbo et al 12 concurred with this study finding, as women required detailed and evidence-based counselling that encompasses the likely side effects and other features of the method.…”
Section: Discussionsupporting
confidence: 85%
“…Even when compared to male condoms (12.8%), implants (69.1%) were by far the most popular modern contraceptive method among sexually active Rwandan female youth. This is surprising given that male condoms are non-invasive and more readily available in small shops and local pharmacies as opposed to implants and other modern methods, which require a visit to a health facility and are frequently preceded by a fear of unwanted effects including fertility interference due to their hormonal nature [ 39 41 ]. These findings contradict Dennis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Even when compared to male condoms (12.8%), implants (69.1%) were by far the most popular modern contraceptive method among sexually active Rwandan female youth. This is surprising given that male condoms are non-invasive and more readily available in small shops and local pharmacies as opposed to implants and other modern methods, which require a visit to a health facility and are frequently preceded by a fear of unwanted effects including fertility interference due to their hormonal nature [39][40][41]. These findings contradict Dennis et al ( 2017), who argue that there is a shift from condoms and pills, which are short-term methods, to injectable contraception and much lower use of long-term methods such as implants and IUD, the reason being that at such a young age, the majority of women are unmarried and having infrequent sex, and thus opting for methods that are easier to use and stop as needed [42].…”
Section: Discussionmentioning
confidence: 99%
“…Even when compared to male condoms (2.1%), implants (12.1%) were by far the most popular modern contraceptive method among sexually active Rwandan female youth. This is surprising given that male condoms are non-invasive and more readily available in small shops and local pharmacies as opposed to implants and other modern methods, which require a visit to a health facility and are frequently preceded by a fear of unwanted effects including fertility interference due to their hormonal nature [35][36][37]. These ndings contradict Dennis et al (2017), who argue that there is a shift from condoms and pills, which are short-term methods, to injectable contraception and much lower use of long-term methods such as implants and IUD, the reason being that at such a young age, the majority of women are unmarried and having infrequent sex, and thus opting for methods that are easier to use and stop as needed [38].…”
Section: Resultsmentioning
confidence: 99%